Chaetanaphothrips kiyosumianus (Thysanoptera, Thripidae) new to India with first record of the male - Tyagi, Kaomud; Kumar, Vikas; Bhuyan, Mantu; Shandilya, Sharadha; Chanda, Sanjoy K. (Zootaxa, 2016)
The male of Chaetanaphothrips kiyosumianus Kudô is diagnosed for the first time along with the first record of this species from India. Molecular data of mitochondrial cytochrome c oxidase (mtCOI) from specimens of this species are also generated as additional data for future studies.